Common components of risk and uncertainty attitudes across contexts and domains: Evidence from 30 countries - Ferdinand M. Vieider; Mathieu Lefebvre; Ranoua Bouchouicha; Thorsten Chmura; Rustamdjan Hakimov; Michal Krawczyk; Peter Martinsson (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
Attitudes towards uncertainty have been indicated to be highly context-dependent, and to be sensitive to the measurement technique employed. We present data collected in controlled experiments with 2939 subjects in 30 countries measuring uncertainty attitudes through incentivized measures as well as survey questions. Our data show clearly that measures correlate not only within decision context or measurements methods, but also across contexts and methods. This points to the existance of one underlying 'risk preference', which influences attitudes independently of the measurement method or choice domain. We furthermore find that answers to a general survey question correlate with incentivized lottery choices in most countries. Much more surprisingly, incentivized and survey measures also correlate significantly between countries. This opens the possibility to conduct cultural comparisons on risk attitudes using survey instruments.
Keywords: D0; D81; C90; J10; 330; risk attitudes; uncertainty attitudes; context-specificity; experimental methodology